Potentiation and recovery following low- and high-speed isokinetic contractions in boys - Chaouachi, A.; Haddad, M.; Castagna, C.; Wong, D. P.; Kaouech, F.; Chamari, K.; Behm, D. G. (Pediatric Exercise Science, 2011)
The objective of this study was to examine the response and recovery to a single set of maximal, low and high angular velocity isokinetic leg extension-flexion contractions with boys. Sixteen boys (11-14 yrs) performed 10 isokinetic contractions at 60°.s-1 (Isok60) and 300°.s-1 (Isok300). Three contractions at both velocities, blood lactate and ratings of perceived exertion were monitored pretest and at 2, 3, 4, and 5 min of recovery (RI). Participants were tested in a random counterbalanced order for each velocity and recovery period. Only a single contraction velocity (300°.s-1 or 60°.s-1) was tested during recovery at each session to remove confounding influences between the recovery intervals. Recovery results showed no change in quadriceps` power at 300°.s-1, quadriceps` power, work and torqueat 60°.s-1 and hamstrings` power and work with 60°.s-1. There was an increaseduring the 2 min RI in hamstrings` power, work and torque and quadriceps` torque with isokinetic contractions at 300°.s-1 suggesting a potentiating effect. Performance impairments during recovery occurred for the hamstrings torque at 60°.s-1 and quadriceps work with 300°.s-1. In conclusion, 10 repetitions of eitherlow or high velocity isokinetic contractions (Isok60 or Isok300) resulted in full recovery or potentiation of most measures within 2 min in boys. The potentiation effect predominantly occurred following the hamstrings Isok300 which might be attributed to a greater agonist—antagonist torque balance and less metabolic stress associated with the shorter duration higher velocity contractions.